The Genus Capillipedium Stapf in India - Raizada, M. B.; Jain, S. K. (Indian Forester, 1951)
History of the nomenclatural complications in the genus Capillipedium Stapf has been reviewed. Reasons for name changes in certain species have been discussed. Six Indian species namely C. paruiflorum ( Br.) Stapf, C. subrepens (Steud.) Henr., C. hugelii ( Hack.) Camus, C.foetidum ( Lisboa) Raizada and Jain, C.filiculmis ( Hook. F. ) Stapf and C. pteropechys ( Clarke) Stapf have been described and illustrated. A new name C.faetidum (Lisboa) Raizada and Jain, based on Andropogon hugeZii Hack. Var.faetidus Lisboa, has been proposed. A statement of name changes in Indian species from Hooker's ( 1896) time onwards has been given in tabular form. Complete bibliography is appended.